Cultural patterns of psychosocial development in late adolescence: a latent profile approach across the United States, Italy, and Taiwan - Troy E. Beckert; ChienTi Plummer Lee; Paolo Albiero; Xiyao Liu (International Journal of Adolescence and Youth)
The aim of this study was to examine the cultural applicability of widely used psychosocial measures and identify patterns of psychosocial development among late adolescents in Taiwan, Italy, and the United States (N = 1,335). Measurement invariance testing revealed partial non-invariance across groups, particularly at the item intercept and factor loading levels. Using latent profile analysis (LPA), four distinct psychosocial profiles emerged within each cultural group, characterized by varying levels of cognitive autonomy, identity development, and shyness. Multigroup LPA indicated that although profile configurations differed across cultures, one profile (Well Balanced) displayed the highest cross-national similarity. Profiles were significantly associated with mental health outcomes including self-worth, depression, and substance use – though such associations were less pronounced in the Taiwanese sample. These findings underscore the need for culturally sensitive tools and profile-based frameworks to understand differences in psychosocial development in a globalized context.